The TSST triggers self-reported stress and biological stress and frustrates basic psychological needs: general and specific buffering effects of physical activity and social support - Schüler, Julia; Rindelhardt, Simona; Ditzen, Beate (Stress, 2025)
Situations characterized by uncontrollability and critical social evaluation frustrate basic psychological needs, as outlined in Self-Determination Theory (SDT). Uncontrollability and social evaluation are central elements of the Trier Social Stress Test (TSST), leading to the hypothesis that the TSST, in addition to increasing self-reported stress and cortisol responses, also frustrates the needs for autonomy, competence, and social relatedness. Participants (N = 195) reported elevated stress and reduced need satisfaction, and increased cortisol responses during the TSST. The roles of assessed physical activity and experimentally-induced social support were also examined. Indeed, in time-sensitive and specific manner, the TSST frustrated basic psychological needs. Social support however mitigated frustration of social relatedness. Physical activity buffered against self-reported stress, the frustration of competence and the cortisol response. Further research is recommended to explore more differentiated interventions that can counteract the negative effects of psychosocial stressors.